Person-Job fit, work related stressors and stress management of call center agents in Iloilo City. - Germo, Beverly S.
One hundred ten (66 Females and 44 Males) contact or call center agenst from three call centers in Iloilo city - ePLDT Ventus, Callbox Inc., and Echo Customer Contact Center, were teseted with Revised Ways of Coping checklist, perceived Stress Scale, and researcher made Person Job Fit Scale., It was found out that a majority of the respondents experienced high levels of stress, and that there exist significant correlations between tenure and two important work related variables which are person job fit and coping. Also, job positions of the agents showed positive correlations with person-job fit, even if job stress, in this study, did not manifest any significant statistical link to person-job fit.